Perbandingan metode ekstraksi maserasi dan sokletasi terhadap kadar fenolik total ekstrak etanol daun sirih (Piper betle L.) secara spektrofotometri visibel. - Priyadi, Agus; Harun , Fatur Rahman; Daulay , Anny Sartika; Ridwanto, Ridwanto (Journal of Pharmaceutical and Sciences, 2025)
Betel leaf (Piper betle L) is a plant widely used as a traditional medicine capable of treating various diseases without causing side effects due to bioactive compounds, one of which is phenolic. This research aims to identify the chemical compounds present in the ethanol extract and determine the total phenolic content of the ethanol extract of betel leaf (Piper betle L). The research method employed is an experimental approach, which includes plant material processing, ethanol extract preparation through maceration and Soxhlet extraction, characterization analysis, phytochemical screening, and determination of the total phenolic content of the ethanol extract of betel leaf using UV-Vis spectrophotometry. The betel leaf extract was prepared using maceration and Soxhlet extraction. The obtained extract was concentrated using a rotary evaporator. Subsequently, the total phenolic content was determined using Visible Spectrophotometry. The phytochemical screening of the ethanol extract of betel leaf revealed the presence of chemical compound groups such as alkaloids, flavonoids, saponins, tannins, steroids or triterpenoids, and glycosides. Total phenolic content was determined by determining the wavelength of gallic acid and operating time, measuring the gallic acid calibration curve, and calculating the total phenolic content using visible spectrophotometry. The results of the total phenolic content determination for the maceration extract were 19.61 ± 0.19716 mg GAE/g, and for the Soxhlet extraction, it was 29.79 ± 1.91040 mg GAE/g.